2014
DOI: 10.1021/ja411233p
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Switchable Rotors in Molecular Crystals with Open Porosity

Abstract: The first example of a porous molecular crystal containing rotors is presented. The permanently porous crystal architecture is sustained by rotor-bearing molecular rods which are connected through charge-assisted hydrogen bonds. The rotors, as fast as 10(8) Hz at 240 K, are exposed to the crystalline channels, which absorb CO2 and I2 vapors at low pressure. The rotor dynamics could be switched off and on by I2 absorption/desorption, showing remarkable change of material dynamics by the interaction with gaseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 48 publications
3
94
0
Order By: Relevance
“…Moreover, while the [D 12 ]TCC2‐ R rate is comparable to other organic frameworks,27, 28, 29, 36 the very fast reorientation rate value obtained for the [D 12 ]TCC3‐ R is larger than in any exclusively organic systems reported previously below ≈200 K (Table S3) 18, 19, 24, 29, 32, 37, 38, 39. In particular, below this temperature, the dynamics of [D 12 ]TCC3‐ R are faster than the ones observed very recently for the para ‐phenylene reorientation in bis(sulfophenylethynyl)‐benzene frameworks based on an overall similar architecture of a phenylene molecular rotor sandwiched between two acetylene moieties (Figure 1 (b)), which previously showed the largest reorientation rate for porous organic materials to date 32…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, while the [D 12 ]TCC2‐ R rate is comparable to other organic frameworks,27, 28, 29, 36 the very fast reorientation rate value obtained for the [D 12 ]TCC3‐ R is larger than in any exclusively organic systems reported previously below ≈200 K (Table S3) 18, 19, 24, 29, 32, 37, 38, 39. In particular, below this temperature, the dynamics of [D 12 ]TCC3‐ R are faster than the ones observed very recently for the para ‐phenylene reorientation in bis(sulfophenylethynyl)‐benzene frameworks based on an overall similar architecture of a phenylene molecular rotor sandwiched between two acetylene moieties (Figure 1 (b)), which previously showed the largest reorientation rate for porous organic materials to date 32…”
supporting
confidence: 63%
“…The larger E a value obtained for [D 12 ]TCC2‐ R versus [D 12 ]TCC3‐ R is again consistent with stronger steric interactions in the terphenylene cage structure. The k 0 values obtained are on the low side of the ≈10 12  Hz22 value often associated with para ‐phenylene rotation, although these values vary significantly with the systems studied and k 0 in the 10 8 –10 41  Hz range are known 19, 23, 24, 27, 28, 29, 32, 36, 37, 40, 41. The associated change in entropy (Δ S ) is negative and is tentatively assigned to correlated rotational motion (Table S2) 41, 42…”
mentioning
confidence: 82%
“…Sozzani and coworkers demonstrated another sophisticated approach to engineer and to control crystalline rotors using porous molecular crystals. 203 The authors demonstrated that permanently porous crystals that incorporate p-phenylene rotors were accessible to small-molecule guests such as CO 2 and I 2 in the vapor phase. In particular, the uptake of I 2 altered the molecular environment of the rotors dramatically: the exchange rate decreased by four orders of magnitude from 10 8 to 10 4 Hz ( Figure 15).…”
Section: Acs Nanomentioning
confidence: 99%
“…[12][13][14][15] With high exposed surface area (inner as well as outer surface) to be attached, porous materials such as zeolites, [16][17][18][19] activated carbon, [20][21][22][23] silica, [24] polymeric materials [25][26][27] and hybrid materials [28] have drawn many interests from scientists for adsorption processes, because they might be good candidates to overcome the obstacles (i.e. [12][13][14][15] With high exposed surface area (inner as well as outer surface) to be attached, porous materials such as zeolites, [16][17][18][19] activated carbon, [20][21][22][23] silica, [24] polymeric materials [25][26][27] and hybrid materials [28] have drawn many interests from scientists for adsorption processes, because they might be good candidates to overcome the obstacles (i.e.…”
Section: Introductionmentioning
confidence: 99%